Network-based statistics for a community driven transparent publication process - Zimmermann, Jan; Roebroeck, Alard; Uludag, Kamil; Sack, Alexander T; Formisano, Elia; Jansma, Bernadette; De Weerd, Peter; Goebel, Rainer (Frontiers in Computational Neuroscience, 2012)
The current publishing system with its merits and pitfalls is a mending topic for debate among scientists of various disciplines. Editors and reviewers alike, both face difficult decisions about the judgment of new scientific findings and possible mistakes or human biases play an unfortunate role in their final verdict. We propose a new community driven publication process that is based on network statistics to make the review, publication and scientific evaluation process more transparent.